Clinicopathological study of breast lesions over a period of one year in a tertiary care center - Neeli, Divyasree; Atla, Bhagyalakshmi; Seeram, Satish Kumar; Latchupatula, Lavanya; Kamireddy, Srikanth Reddy (International Journal of Research in Medical Sciences, 2018)
Background: Breast carcinoma is no longer seen as a single disease but rather a multifaceted disease comprised of distinct biological subtypes with varied natural history, presenting a diverse spectrum of clinico-pathological and molecular features with different therapeutic and prognostic implications. The present study was designed to evaluate the frequency, age, gender and histopathological features of breast carcinoma in a tertiary care hospital. Methods: The present study is a hospital based retrospective study for a period of one year from January 2015 to December 2015, conducted in the Department of Pathology, Andhra Medical College, Visakhapatnam.The clinical details were recorded as per the proforma. Tissue for H&E sections were fixed in 10% formalin and subjected to routine paraffin embedded processing and stained with Hematoxylin and Eosin. Results: Out of the total 185 cases of breast lesions, 151 cases (81.62%) were diagnosed as non-malignant and 34 cases were malignant (18.37%). Maximum number of patients, 106 cases (57.2%), were between 21 - 40 years. Out of 34 malignant breast lesions, 27 were diagnosed as Infiltrative duct cell carcinoma (79.41%), followed by medullary carcinoma 4 cases (11.76%). Conclusions: The pattern of breast lesions provides valuable information concerning clinicopathological profile of breast lesions. The clinical diagnosis of a breast lump must be correlated with histopathological diagnosis for correct and adequate treatment of patient.